A new method to assess fetal head descent in labor with transperineal ultrasound - Barbera, A. F.; Pombar, X.; Perugino, G.; Lezotte, D. C.; Hobbins, J. C. (Ultrasound in obstetrics & gynecology, 2009)
Objectives To assess the feasibility and reproducibility of measuring fetal head station and descent during labor using transperineal ultrasound (TPU) imaging, to compare the evaluation of fetal station through digital examinations with concurrent TPU assessments, and to assess its utility in distinguishing patients whose pregnancy will result in spontaneous vaginal delivery from those who will require operative vaginal delivery or Cesarean section for failure to progress. Methods TPU and digital examinations were performed in 88 term laboring patients with a singleton fetus in cephalic presentation. Using TPU imaging, head descent was quantified by measuring the angle between the long axis of the pubic symphysis and a line extending from its most inferior portion tangentially to the fetal skull. Intraobserver and interobserver variability were calculated using variance component analysis. TPU imaging was used to measure the angle of head descent during the second stage of labor in 23 of the women. Results Analysis of replicated measurements on 75 subjects, by the same observer at approximately the same time, yielded an average SD (intraobserver variability) of approximately 2.9° for the measurement of angle of head descent on TPU examination. A separate variance component analysis on a subset of 15 assessments for which measurements were repeated by a second observer, with two to four replicate measurements obtained by each, yielded an interobserver error estimate of 1.24°. A significant linear association was found between clinical digital assessments and measurement of angle of head descent by TPU examination (P < 0.001). An angle of at least 120° measured during the second stage of labor was always associated with subsequent spontaneous vaginal delivery. In six pregnancies ending in Cesarean section the mean angle of descent measured at last TPU examination was only 108°. Conclusions The angle of head descent measured by TPU imaging provides an objective, accurate and reproducible means for assessing descent of the fetal head during labor. Copyright © 2009 ISUOG. Published by John Wiley & Sons, Ltd.